Reductive activation of O-2 by a bioinspired Fe complex for catalytic epoxidation reactions - Singh, Kundan K.; Sen Gupta, Sayam (Chemical Communications, 2017)
Aerobic epoxidation of olefins catalyzed by iron complexes without the use of a sacrificial coreductant is unknown. We report the reductive activation of O-2 by a bioinspired [(bTAML)Fe-III(H2O)](-) (1) complex to catalyze the epoxidation of alkenes with TONs of up to 80. Spectroscopic and kinetic evidence indicates the involvement of FeV(O) as the active oxidant during the reaction.